2018
DOI: 10.1007/s10826-017-1000-5
|View full text |Cite
|
Sign up to set email alerts
|

Parental Reflective Functioning Affects Sensitivity to Distress in Mothers with Postpartum Depression

Abstract: Parental reflective functioning (PRF) refers to the capacity of caregivers to reflect upon their children's internal mental states and intentions, which is seen as crucial for parental sensitivity, defined as the adequate behavioral response to an infant's signals. In this study, the effect of maternal PRF on sensitivity during the mother-infant interaction was examined in a clinical sample of 50 mothers who were experiencing postpartum depression and their infants aged three to ten months. Mother and infant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 63 publications
12
59
0
Order By: Relevance
“…Another limitation concerns the low internal consistency of the PRFQ subscale pre-mentalizing for both time points. Earlier research has found acceptable internal consistency for this subscale [56], but also internal consistency in the low range [68]. One possibility for the low reliability in our data may be that some of the questions were difficult for parents to answer at this early stage of infancy since the scale is designed for parents of children up to several years old [56].…”
Section: Strengths and Limitationsmentioning
confidence: 58%
“…Another limitation concerns the low internal consistency of the PRFQ subscale pre-mentalizing for both time points. Earlier research has found acceptable internal consistency for this subscale [56], but also internal consistency in the low range [68]. One possibility for the low reliability in our data may be that some of the questions were difficult for parents to answer at this early stage of infancy since the scale is designed for parents of children up to several years old [56].…”
Section: Strengths and Limitationsmentioning
confidence: 58%
“…Another limitation concerns the low internal consistency of the PRFQ subscale pre-mentalizing for both time points. Earlier research has found acceptable internal consistency for this subscale (56), but also internal consistency in the low range (65). One possibility for the low reliability in our data may be that some of the questions were difficult for parents to answer at this early stage of infancy since the scale is designed for parents of children up to several years old (56).…”
Section: Strengths and Limitationsmentioning
confidence: 58%
“…Another limitation concerns the low internal consistency of the PRFQ subscale pre-mentalizing for both time points. Earlier research has found acceptable internal consistency for this subscale (56), but also internal consistency in the low range (68). One possibility for the low reliability in our data may be that some of the questions were di cult for parents to answer at this early stage of infancy since the scale is designed for parents of children up to several years old (56).…”
Section: Strengths and Limitationsmentioning
confidence: 60%